Effects of Acute Endurance Exercise on Plasma Protein Profiles of Endurance-Trained and Untrained Individuals over Time. (30th April 2016) - Schild, Marius; Eichner, Gerrit; Beiter, Thomas; Zügel, Martina; Krumholz-Wagner, Ilke; Hudemann, Jens; Pilat, Christian; Krüger, Karsten; Niess, Andreas M.; Steinacker, Jürgen M.; Mooren, Frank C.
Abstract : Acute physical exercise and repeated exercise stimuli affect whole-body metabolic and immunologic homeostasis. The aim of this study was to determine plasma protein profiles of trained (EET, n = 19 ) and untrained (SED, n = 17 ) individuals at rest and in response to an acute bout of endurance exercise. Participants completed a bicycle exercise test at an intensity corresponding to 80% of theirV O 2 m a x . Plasma samples were taken before, directly after, and three hours after exercise and analyzed using multiplex immunoassays. Seventy-eight plasma variables were included in the final analysis. Twenty-nine variables displayed significant acute exercise effects in both groups. Seven proteins differed between groups, without being affected by acute exercise. Among these A2Macro and IL-5 were higher in EET individuals while leptin showed elevated levels in SED individuals. Fifteen variables revealed group and time differences with elevated levels for IL-3, IL-7, IL-10, and TNFR2 in EET individuals. An interaction effect could be observed for nine variables including IL-6, MMP-2, MMP-3, and muscle damage markers. The proteins that differ between groups indicate a long-term exercise effect on plasma protein concentrations. These findings might be of importance in the development of exercise-based strategies in the prevention and therapy of chronic metabolic and inflammatory diseases and for training monitoring.